Analisis manajemen risiko pada bank syariah: Membangun keberlanjutan dalam sistem keuangan Islami - Tyas, Ifadatul Laili Kusumaning (Maliki Interdisciplinary Journal, 2024)
Risk management is a key aspect of sharia banking operations, which aims to ensure operational sustainability, compliance with Islamic principles, and effective risk management. The risks faced by sharia banks include operational risks, credit, liquidity, law, reputation, strategy, markets and compliance. This analysis uses a qualitative approach where the data sources used come from books, scientific journals as well as previous research. The analysis of this investigation is that in order to manage these risks, sharia banks must adopt a proactive and cautious approach, as well as prioritize compliance with sharia principles. The importance of risk management in sharia banks is not only related to operational and financial sustainability, but also toining the confidence of customers and the general public in the sharia bank as a financial institution in line with sharia principles. Therefore, the implementation of effective risk management in accordance with the principles of Shariah becomes a must for shariah banks to maintain their stability, compliance, and reputation.